Ekofeminisme pada Tokoh San dalam film “Princess Mononoke” Karya Sutradara Hayao Miyazaki - Alisca Putri Dirgantari (Pascasarjana ISBI Bandung, 2020)
This study focuses on the perspective of eco-feminism as a theory of environmental ethics in the film